Control of a modular multilevel converter with pulsed DC load - Jankovic, Marija; Watson, Alan James; Costabeber, Alessando; Clare, Jon C. (2016)
This paper focuses on a Modular Multilevel Converter grid interface for a klystron modulator system that behaves as a pulsed DC load. With such a load, and without mitigating control, the MMC suffers from cell capacitor voltage imbalance between the converter arms which leads to distortion (fluctuation) of the absorbed AC power. This paper proposes an augmented modulation strategy, with a tailored distribution of the modulation signals between the arms within a phase, to ensure low AC power fluctuation. The effectiveness of the method has been verified through simulation and has been experimentally proven on a 7 kW MMC prototype operating with a 3 kA pulsed DC load.